2014
DOI: 10.1088/0953-8984/26/4/045303
|View full text |Cite
|
Sign up to set email alerts
|

Divacancies in carbon nanotubes and their influence on electron scattering

Abstract: First-principles calculations are applied to study the formation energies of various divacancy defects in armchair and zigzag carbon nanotubes of varying diameter, and the transport properties for the corresponding structures. Our explicit ab initio calculations confirm that the lateral 585 divacancy is the most stable defect in small diameter tubes, with the 555 777 divacancy becoming more stable in armchair tubes larger than (30, 30). Evaluating the electron transmission as a function of diameter and chirali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In the past, most theoretical work in the field of quantum transport simulations focused on the properties of single selected CNTs, like it was done for vacancies [Bie05,Bie08,Flo08,Gre14,Lee12], substitutional atoms [Kho09,Roc08] and functionalizations [Lop13,Bla10,Lop10, Lop09,Roc08]. For this purpose, different electronic structure methods were addressed, from tight binding (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, most theoretical work in the field of quantum transport simulations focused on the properties of single selected CNTs, like it was done for vacancies [Bie05,Bie08,Flo08,Gre14,Lee12], substitutional atoms [Kho09,Roc08] and functionalizations [Lop13,Bla10,Lop10, Lop09,Roc08]. For this purpose, different electronic structure methods were addressed, from tight binding (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Divacancies are also classified as lateral or vertical depending on the orientation of the pentagons along or perpendicular to the nanotube axis, respectively. Lateral divacancies are generally more stable than vertical divacancies in SWCNTs,42 and thus only lateral divacancies are considered here. For the adatom system, we considered the bridge position of the carbon atom linking two equivalent adjacent sites oriented along the nanotube axis (Figure 1 d).…”
Section: Resultsmentioning
confidence: 99%
“…Previous experiments, in which defects were created by ion irradiation, indicate that for long CNTs the strong localization regime can be achieved, where the conductance decreases exponentially with the CNT length [9]. This was also studied theoretically for different defect types [17][18][19][20][21][22], especially for vacancies [23][24][25][26][27], and also for other materials like silicon nanowires [28]. First analytic derivations of White and Todorov showed that the localization exponent depends linearly on the tube diameter [29].…”
Section: Introductionmentioning
confidence: 92%